Writing against war and occupation in Iraq: Gender, social critique and creative resistance in Dunya Mikhail's The War Works Hard. Issue 1 (1st August 2010) - Mehta, Brinda
Dunya Mikhail's collection of war poetry The War Works Hard reveals the double eclipsing suffered by women, first as Iraqis, and then as Iraqi women, during the current crisis in Iraq. This marginalization constitutes another war crime in the form of a tacit yet complicit agreement between colonizers and resistors to achieve their self-defined goals of liberation at the expense of women. Using Nawal El Saadawi's concept of 'dissidence and creativity', I demonstrate how Mikhail's poetic testimony of the war unsettles the reader with its probing existential meditations on the human cost of war and sanctions. The collection represents a crucial feminized intervention in war poetry to relate the anguish of mothers, wives and daughters, the search for place and identity and the sense of displacement occasioned by exile and occupation. While all forms of creative resistance such as literature, cinema, dance, art and music represent valuable acts of resistance, this essay makes the case that poetry goes beyond the limits of the possible (and acceptable) by its ability to resonate with a certain 'vibration' of thought and feeling. As an oral narrative, poetry eludes borders and boundaries to imagine its own sensorial landscapes. Poetry penetrates the very depths of the unconscious to revive repressed memories, expose gaping wounds, provide healing in moments of despair, connect with the wonders of nature in an 'unnatural' environment of fear and violence, and to celebrate the spirit of survival in commemorative verse. In other words, poetry, as a form of creative resistance, becomes an urgent call to action in situations of domination and anarchy, through its articulation of a sense of ethical consciousness. In so doing, poetry gives voice to traumatic experience and the un-nameable, this precarious non-dit, resisting transliteration in conventional language.